Sci‐Hub: The new and ultimate disruptor? View from the front - Nicholas, David; Boukacem‐Zeghmouri, Chérifa; Xu, Jie; Herman, Eti; Clark, David; Abrizah, Abdullah; Rodríguez‐Bravo, Blanca; Świgoń, Marzena (Wiley, 2019)
The Harbinger project was a 3-year-long international study of the changing attitudes and behaviours of early career researchers (ECRs). One of the aims of the project was to discover if ECRs were adopting disrupting platforms that, legitimately or illegitimately, promote openness and sharing. It has been alleged that such an adoption appeals to them as Millennials. More than 100 ECRs from seven countries were questioned annually, and questions about Sc-Hub were raised as part of discussions about discovery and access. Interview data were supplemented by desk research and Google Trends statistics. It was found that Sci-Hub use was increasing and that a quarter of the ECRs now use it, with French ECRs being the biggest users. However, Sci-Hub is making little headway with ECRs from the UK, USA, Malaysia, and China, although in China's case, this can be explained by it being banned and the country having its own equivalent, www.91lib.com. Sci-Hub is used as much for convenience as necessity; use is not connected to the strength of library provision and and it has been suggested that it represents a bigger threat to publishers than ResearchGate, whose star might be waning. © 2018 The Author(s). Learned Publishing © 2018 ALPSP.